Albright's Hereditary Osteodystrophy: A Constellation of Clinical Features - L Ambika; Vaishali Keluskar (Wolters Kluwer Medknow Publications, 2010)
Pseudohypoparathyroidism (PHP) is an inherited metabolic disorder characterized by end-organ resistance to the action of PTH (Parathyroid Hormone). There are four types of PHPs namely Ia, lb, Ic and II. PHP Ia is associated with a constellation of clinical features referred to as Albright's Hereditary Osteodystroohy (AHO). The oral manifestation of AHO found in the literature includes aplasia and or enamel hypoplasia, late tooth eruption and enlarged radicular channels susceptible to caries. Here, we are reporting a rare case of a 14-year-old girl with Albrigt's hereditary osteodystrophy with disintinctive oral manifesitations.